Implementasi Game Edukasi Untuk Meningkatkan Pemahaman Siswa Dalam Pembelajaran PAI Di Era Digital - Abdillah, Muhammad Ilham; Luqna Hunaida, Wiwin; Muqit, Abdul (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the implementation of educational games in Islamic Education (PAI) learning in the digital era to improve students' understanding at SMPN 1 Krian. The use of educational games such as Kahoot! and Quizizz was chosen to create an interactive and enjoyable learning experience, focusing on increasing student engagement and strengthening understanding of PAI concepts such as fiqh, aqidah, and morality. This research uses a qualitative-descriptive approach, where data were collected through observations, interviews with teachers and students. The results show that the use of educational games in PAI learning successfully increased students' learning motivation, deepened their understanding of the material taught, and created a more dynamic learning atmosphere. Instant feedback provided through educational game platforms helped students quickly correct their mistakes and enhanced active participation in class. Thus, the implementation of educational games has proven effective in supporting PAI learning at SMPN 1 Krian and is relevant to technological developments in the digital era.